E-integrator of LBP-Provider of Logistics Barter - V. Gabdullin, Lenar; A. Bikulov, Rinat; M. Khamitov, Ilnaz; S. Stepanova, Yuliya (International Journal of Engineering and Technology, 2018)
Logistic barter is a normal commodity exchange among producers where one thing is exchanged to another without monetary pay on the basis of globally integrated trade procedure. The approach of barter logistics is not abandon money, however ignores it among producers.Â  Logistics has touched and touches such heights, while the requirement for a "universal equivalent of goods" among producers could simply cease to exist [1]. A powerful combination of logistics and e-commerce is expected to lead to significant changes in the overall business landscape. E-commerce will provide an opportunity for many companies to make the necessary communications and conclude transactions with each other, and logistics will provide an opportunity to more effectively use this information to manage activities in their business. Instead of a two-way relationship between the supplier and the customer, the business will increasingly be based on networks of supply chains, made up of groups of suppliers and customer groups [2]. E-commerce, e-sourcing, e-markets are better to be united under the auspices of logistics barter into an e-integrator, which will be the serving element of the LBP-provider. An e-integrator is an integrator of information and communication technologies for supply chains of logistics barter, in the form of electronic means, taking into account a closing link, e-commerce, and the reverse distribution of added value. The paper describes the new LBP-providers which are not a servicing element of the economy, but become operators of an alternative economy themselves. We have also considered the basics for the mathematical concept of a future LBP (logistic barter) operator.Â Â